2015
DOI: 10.1155/2015/934623
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practice, and Barriers of Foot Care among Diabetic Patients Attending Felege Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia

Abstract: Introduction. Diabetes mellitus is a chronic debilitating condition characterized by an increased blood glucose level and is associated with significant morbidity, mortality, and increasing health care cost. Diabetic foot ulcers and lower extremity amputations are a common, complex, costly, and disabling complication of diabetes. An estimated 15% of patients with diabetes develop a lower extremity ulcer. Objective. The aim of this study was to assess knowledge, practice, and barriers of diabetic foot self-care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
72
6
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(107 citation statements)
references
References 12 publications
14
72
6
15
Order By: Relevance
“…Seid et al, in his study, observed that 41.2% patients checked their legs every day and 60% pat dry their legs after washing. 20 In present study, 85% participants did not walk bare foot, which is comparable with observation made by Dikeukwu RA et al that 82% respondents did not walk bare foot. 22 Similarly, Lutfi ARM et al, also mentioned in his study that 77.1 % patients did not walk bare foot.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Seid et al, in his study, observed that 41.2% patients checked their legs every day and 60% pat dry their legs after washing. 20 In present study, 85% participants did not walk bare foot, which is comparable with observation made by Dikeukwu RA et al that 82% respondents did not walk bare foot. 22 Similarly, Lutfi ARM et al, also mentioned in his study that 77.1 % patients did not walk bare foot.…”
Section: Discussionsupporting
confidence: 91%
“…As per the observation done by Seid A et al in his study, 95.8% of the respondents were aware about the frequency of washing their feet. 20 In present study, only 33% respondents knew that the temperature of water should be checked before using it. Similar findings were observed by AR Muhammad Lutfi et al in their study in which 31 % respondents knew about this.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Diabetic foot ulcer (DFU) is a full thickness wound penetrating through the dermis located below the ankle in a diabetes which can become infected it is untreated [6]. Foot ulcer is one the major complications diabetes patients have which can be prevented with good care of feet.…”
Section: Introductionmentioning
confidence: 99%
“…All patients, if given proper guidance and education regarding foot care, should be able to make significant improvements in their foot care [15]. It has been estimated that up to 50% of the major amputations in diabetic patients can be prevented with effective education [6].…”
Section: Introductionmentioning
confidence: 99%